Levels of Complexity in Mathematics Teachers’ Knowledge Connections: An Approach Based on MTSK and Piaget’s Schemas - Estela Juárez-Ruiz; Eric Flores-Medrano; Keylla Otero-Valega; Lina Tascón-Cardona (Education Sciences)
This paper presents a study whose aim was to formulate a conceptual framework that allows us to understand the degree of complexity of the connections between the knowledge that a mathematics teacher can possess, based on the model of the mathematics teacher’s specialized knowledge model and the Piaget’s schemas. To this end, a literature review was carried out to analyze how these connections are made in the minds of mathematics teachers and how complex they are, identifying a deficit. Therefore, the schema structure proposed by Piaget, with its three stages of intra-, inter-, and trans-development, was considered. Based on an instrumental case study with two prospective teachers, an analysis was performed on semi-structured interviews conducted while the teachers separately discussed a lesson plan based on the understanding of multiplication and division of natural numbers, aimed at third-grade students. The results show that three types of knowledge schemas emerged among the participating teachers, with the respective types of connections between the knowledge. This shows that the connections between the knowledge of the model in teachers’ minds can vary in complexity.